Rapid SNP genotyping, sex identification, and hybrid-detection in threatened bull trout - Stephen J. Amish; Shana Bernall; Patrick DeHaan; Michael Miller; Sean O’Rourke; Matthew C. Boyer; Clint Muhlfeld; Angela Lodmell; Robb F. Leary; Gordon Luikart (Conservation Genetics Resources, 2022)

No evidence for ecological segregation protecting native trout from invasive hybridization - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)

Legacy introductions and climatic variation explain spatiotemporal patterns of invasive hybridization in a native trout - Clint C. Muhlfeld; Ryan P. Kovach; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)
Hybridization between invasive and native species, a significant threat to worldwide biodiversity, is predicted to increase due to climate‐induced expansions of invasive species. Long‐term research and monitoring are crucial for understanding the ecological and evolutionary processes that modulate the effects of invasive species. Using a large, multidecade genetics dataset ( N = 582 sites, 12,878 individuals) with high‐resolution climate predictions and extensive stocking records, we evaluate the spatiotemporal dynamics of hybridization between native cutthroat trout and invasive rainbow trout, the world's most widely introduced invasive fish, across the Northern Rocky Mountains of the United States. Historical effects of stocking and contemporary patterns of climatic variation were strongly related to the spread of hybridization across space and time. The probability of occurrence, extent of, and temporal changes in hybridization increased at sites in close proximity to historical stocking locations with greater rainbow trout propagule pressure, warmer water temperatures, and lower spring precipitation. Although locations with warmer water temperatures were more prone to hybridization, cold sites were not protected from invasion; 58% of hybridized sites had cold mean summer water temperatures (

Near absence of hybridization between sauger and introduced walleye despite massive releases - Daniel M. Bingham; Robb F. Leary; Sally Painter; Fred W. Allendorf (Conservation Genetics, 2012)

Cutthroat Trout Hybridization and the U.S. Endangered Species Act: One Species, Two Policies - FRED W. ALLENDORF; ROBB F. LEARY; NATHANIEL P. HITT; KATHY L. KNUDSEN; MATTHEW C. BOYER; PAUL SPRUELL (Conservation Biology, 2005)

Intercrosses and the U.S. Endangered Species Act: Should Hybridized Populations be Included as Westslope Cutthroat Trout? - FRED W. ALLENDORF; ROBB F. LEARY; NATHANIEL P. HITT; KATHY L. KNUDSEN; LAURA L. LUNDQUIST; PAUL SPRUELL (Conservation Biology, 2004)
There are currently no policy guidelines for treating hybrids under the U.S. Endangered Species Act (ESA). We considered the scientific basis for determining whether hybridized populations should be included as part of the westslope cutthroat trout ( Oncorhynchus clarki lewisi ) unit considered for listing under the ESA. Westslope cutthroat trout are threatened by genomic extinction because of widespread introgressive hybridization with introduced rainbow trout ( O. mykiss ) and Yellowstone cutthroat trout ( O. c. bouvieri ). Experimental results suggest that first‐generation hybrids between westslope cutthroat trout and rainbow trout have reduced fitness. However, hybridization may spread even when hybrids have severely reduced fitness because the production of hybrids is unidirectional—that is, all the progeny of a hybrid will be hybrids. In addition, heterosis resulting from the sheltering of deleterious recessive alleles in early‐generation hybrids may increase the effective rate of introgression. However, such short‐term increases in fitness may disrupt important long‐term adaptations of native populations. The loss of these adaptations will be difficult to detect because some local adaptations might only be apparent during periodic episodes of extreme environmental conditions, such as winter storms, drought, or fire. Thus, rapid spread of hybridization could result in the loss of local adaptations in native populations of westslope cutthroat trout and decrease their probability of long‐term persistence. Protection of populations with some admixture would protect sources of spreading hybridization. Treatment of hybrids in conservation planning depends primarily on the amount of evolutionary divergence between the hybridizing taxa and the geographical extent of introgression. We recommend that only nonhybridized populations be included as westslope cutthroat trout in the unit to be considered for listing. Populations of unknown status should be protected until more information about these populations becomes available.